2012
DOI: 10.1590/s0103-507x2012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Incidência e principais causas de extubação não planejada em unidade de terapia intensiva neonatal

Abstract: Incidence and primary causes of unplanned extubation in a neonatal intensive care unit Incidência e principais causas de extubação não planejada em unidade de terapia intensiva neonatal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
1
2
0
12
Order By: Relevance
“…23 The percentage of 7.88% of patients demonstrates what was expected according to the literature, however, reducing to the minimum possible, around 2%, is the desired. 23 About 65.38% of the patients who required reintubation were unable to perform spontaneous ventilation outside the mechanical ventilator due to their clinical condition. Consequently, they were exposed to the complications of this AE.…”
supporting
confidence: 53%
“…23 The percentage of 7.88% of patients demonstrates what was expected according to the literature, however, reducing to the minimum possible, around 2%, is the desired. 23 About 65.38% of the patients who required reintubation were unable to perform spontaneous ventilation outside the mechanical ventilator due to their clinical condition. Consequently, they were exposed to the complications of this AE.…”
supporting
confidence: 53%
“…As principais causas analisadas foram agitação e manipulação inadequada do paciente durante a execução de alguns procedimentos, fixação e posicionamento inadequado do tubo endotraqueal (TET), dentre outros. Diante disso, descreve que é necessária a adoção de medidas para diminuir este evento (17) . Nesta mesma perspectiva, o artigo 02 apresenta um pacote de práticas que podem ser implementadas para reduzir as ENP, como a educação do pessoal, a frequência e importância de ENP, priorizando a segurança do TET, colocação de cartões coloridos para alertas de vias aéreas na cabeceira de cada paciente entubado e/ou ventilado mecanicamente, uso de um dispositivo comercial para proteger o tubo e a análise de qualquer ENP por uma equipe multidisciplinar.…”
Section: Discussionunclassified
“…Low birth weight is a paradox among social classes, as the difference in the prognosis of mortality is evident since the low birth weight newborns' mortality rate is higher in places with low socioeconomic status. 25 Studies in Turkey and Camões showed that neonatal deaths were related to prematurity and its consequences, different heart diseases or genetic and congenital anomalies, infections, and asphyxia. Another study carried out in China found that newborns with congenital anomalies increased the odds of death by 50%, compared to those who did not have this anomaly.…”
Section: Factors Associated With the Prognosis Of Newborns In Nicusmentioning
confidence: 99%